Human mu-opioid receptor overexpressed in baculovirus system and its pharmacological characterizations - Wei Qiang; Zhou De-He; Shen Qing-Xiang; Wang Chun-He; Chen Jie; Li Chang-Lin; Pei Gang; Chi Zhi-Qiang (Acta Pharmacologica Sinica; Vol 19, No 3 (May 1998): Acta Pharmacologica Sinica, 2016)
AIM: To overexpress human mu-opioid receptor (muOR) with characteristics similar to those of mammalian origin. METHODS: Human muOR with a tag of 6 consecutive histidines at its carboxyl terminus was expressed in recombinant baculovirus infected Sf9 insect cells. Then the pharmacological characterizations of the product were studied by receptor binding assay and cAMP assay. RESULTS: The maximal binding capacity for the [3H]diprenorphine and [3H]ohmefentanyl (Ohm) were 9.1 +/- 0.7 and 6.52 +/- 0.23 nmol/g protein, respectively. The [3H]diprenorphine or [3H] Ohm binding to the receptor expressed in Sf9 cells was strongly inhibited by alpha-selective agonists [D-Ala2, N-methyl-Phe4, glyol5] enkephalin (DAGO), Ohm, and morphine, but neither by the delta-selective agonist [D-Pen2, D-Pen5] enkephalin (DPDPE) nor by the kappa-selective agonist ¿trans-(+/-)-3, 4-dichloro-N-methyl-N-[2-(1-pyrrolidinyl) cyclohexyl]¿ benzacetamide (U50488). NaCl 100 mmol.L-1 and guanosine triphosphate (GTP) 50 mumol.L-1 could reduce mu agonists Ohm and etorphine affinity binding to the expressed muOR. DAGO and Ohm effectively inhibited forskolin-stimulated cAMP accumulation. This agonist-dependent effect was blocked by opioid antagonist naloxone. CONCLUSION: The overexpression of human muOR with a tag of six consecutive histidines at its carboxyl terminus in Sf9 insect cells retained the characteristics of wild-type human muOR.